Título Padrão - Kempf, Morc; Matthews, Henry Ramos (Arquivos de Ciências do Mar, 2018)
This note is based on material collected by the brazilian Navy R/V "Almirante Saldanha" in the North and Northeast of Brazil, during the months of October-December, 1967 . The investigated area covers the continental shelf, the oceanic islands and banks offshore, between latitudes 05°03'N and 07°30'S (figure 1) . The material was obtained by means of dredgings and trawlings. Indications on the nature of the bottom and stations list are given in a paper by Kempf, Coutinho & Morais (1968, in print).